Food safety standards in the Guatemalan fresh pea sector: The role of financial literacy in technology adoption - Anna K. Müller; Ludwig Theuvsen (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2015)
The transformation of the global agrifood system is characterized by the increasing importance of food safety and quality standards. This trend is challenging farmers in countries like Guatemala as they lack necessary skills and assets. This study analyzes the determinants of Globalgap adoption with a special focus on financial literacy. The concept has not been considered yet in technology adoption studies. Our results indicate that financial literacy indeed has a significant impact on the probability to adopt the standard. Our results hold practical implications for development interventions targeting technology and standard adoption and smallholder market integration.
Keywords: Q14; Q12; Q16; O33; C38; C31; 330; Technology adoption; food safety standards; financial literacy; developing countries; market integration